Social Humanoid Robot dalam Perspektif Syariat dan Etika - Kartika, Dwi; Saiful Bahri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Social humanoids robots are robots designed to interact with people in a manner resembling interaction betweenn humans, with the appearance and manners resembling that of man. This study looking at the use of social humanoids robots from the perspektive of islam and ethics, to ensure that this technology used by way in accordance with religious and moral. The perspektive of islam the use of these robots acceptable for used in the right people, as in the helath sector, education, and public services. Islam teaches that everything is benefecial to mankind and not break acceptable. But is also stressed in creating an image or effigy that imitates life, although robots used for the purpose of education or medical and not treated as living creatures acceptable. It is also vital to keep interaction in islamic culuture and attitude with robot. Make sure that privacy and dignity of the individual are not violated. Ethically the use of social humanoid robots should consider the social impact. Justice and human well being as a whole, this technology should help relieve human work without causing mass unemployment, maintains physical and user data, and don’t overplace human interactions with other human beings. Robot must be designed and programmed to treat humans with respect, not to manipulate emotional or unethical human decisions.